A Monte Carlo Method to Quantify the Effect of Reactor Residence Time Distribution on Polyolefins Made with Heterogeneous Catalysts: Part IV—Intraparticle Transfer Resistance Effects. Issue 6 (4th October 2018) - Liu, Bao; Liu, Boping; Soares, João B. P.
Abstract: An integrated Monte Carlo/polymeric multilayer model (MC/PMLM) is developed to predict the polymer particle size distribution (PSD) and microstructures of polyolefins made with heterogeneous catalysts under intraparticle mass transfer limitations. The Monte Carlo model is used to randomly sample particle sizes and residence times from the catalyst PSD and reactor residence time distribution (RTD), respectively, while the polymeric multilayer model is used to describe single‐particle growth considering intraparticle mass transfer resistances. The effect of reactor RTD, catalyst PSD, and polymerization kinetics on polymer PSD and polymer properties is systematically investigated with the MC/PMLM for the first time. The results show that intraparticle mass transfer limitations under various operating conditions may affect polymer PSD and polymer properties. In addition, due to the versatility of the Monte Carlo approach, the proposed MC/PMLM is adequate to describe complex cases, such as reactor systems with arbitrary RTD and catalyst particles having any PSD. Abstract : An integrated Monte Carlo and polymeric multilayer model (MC‐PMLM) is developed to predict the polymer PSD and microstructure information in a solid‐catalyzed olefin polymerization process, while taking the intraparticle mass transfer resistance into consideration. The proposed MC‐PMLM can deal with very complex scenarios with any shape of catalyst PSD and reactor RTD, under distinct polymerization kinetics.